Dihydropyridine receptor of L-type Ca2+ channels: identification of binding domains for [3H](+)-PN200-110 and [3H]azidopine within the alpha 1 subunit. - Striessnig, J (1991)
To identify the binding domain for dihydropyridine Ca2+ antagonists, skeletal muscle Ca2+ channels were photolabeled with [3H](+)-PN200-110 and [3H]azidopine. Regions of alpha 1 photolabeled by these ligands were then identified by antibody mapping of proteolytic fragments. Approximately 50% of the specific labeling by both ligands was incorporated in domain III. [3H]Azidopine labeled peptide Gln-989-Arg-1022, which contains a portion of the connecting loop between transmembrane segments IIIS5 and IIIS6 (IIIS5/S6), and peptide Ala-1023-Lys-1077, which contains IIIS6 itself and some adjacent amino acid residues. In contrast, [3H](+)-PN200-110 labeling occurred almost exclusively in the fragment containing IIIS6. A second site labeled by both ligands was identified in transmembrane segment S6 of domain IV and adjacent residues. In contrast to azidopine, the photoreactive benzofurazane group of (+)-PN200-110 is located in close proximity to the essential dihydropyridine ring. Therefore, the regions photolabeled by [3H](+)-PN200-110 within or adjacent to transmembrane segments IIIS6 and IVS6 must participate in the formation of the dihydropyridine binding site. As IIIS5/S6 is preferentially labeled by [3H]azidopine, it may contribute to drug binding by interaction with the long side chain of some dihydropyridines like azidopine. It is proposed, based on physiological studies, that these three peptide segments interact to form a receptor site accessible from the extracellular surface of the Ca2+ channel.